DAKWAH PERSPEKTIF TABLIGH: KADERISASI MUBALIGH PENULIS - Kusnawan, Aep (Fakultas Dakwah IAIN Purwokerto, 2007)
Tabligh, a massive da’wa, can be done in various activities, one o f which is through writings in mass media. The increasing number of mass media, such as newspapers, tabloids, magazines, sh'ows iriformation and transparency era. Thepower of information conveyed by mass media is so dominant that it is necessaryfor mubaligh’s (preachers) to concem with this field. Otherwise, readers will be influenced by the messages in the media which are usually lack of religious values. For that reason, CWC (Creative Writing Club) is offered to develop mubaligh’s writing skills. It starts with the urgency and the power of writing and continued with how to develop, socialize, and train writing skills as well as other techniques related to CWC to be practiced.